Local Wisdom-Based Cultural Conservation as an Effort to Preserve and Develop Tourism Villages Through Traditional Music Training in Sukaharja Village, Sukamakmur District, Bogor, West Java (Current Research in Education: Conference Series Journal, 2024)
Sukaharja Tourism Village, located in Sukamakmur District, Bogor Regency, West Java, is a village with significant potential being developed through a community-based tourism concept to achieve sustainability. This village leverages its natural, cultural, and social assets through an educational tourism model based on local wisdom, including agriculture, animal husbandry, culinary arts, and nature tourism. However, the arts sector, specifically degung music (a traditional Sundanese orchestra), has not been optimally utilized to support the village's promotion and development. Although a full set of degung gamelan instruments is available at the village hall, its use in promotional events remains minimal. Observing this situation, the researcher is motivated to conduct a culture conservation initiative based on local content, focusing on the development of the traditional degung art. The goal is to preserve this Sundanese cultural heritage while simultaneously supporting the tourism village's growth. Through traditional music training, this effort aims to maximize degung art’s potential as a tourist attraction that boosts the local economy, preserving culture while contributing to Sukaharja Village’s welfare through sustainable tourism.